2004
DOI: 10.1039/b404899g
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for streamlined release identity testing of chromatography media

Abstract: In accordance with the US Code of Federal Regulations 21CFR 211.84 (6)(d)(1), a specific identity test must be performed for the release of chromatography media (stationary phase) before use in production of human pharmaceuticals. Due to the complexity of the physical and chemical properties of these media, i.e., variable particle morphology, insolubility, and chemical inertness, the development of specific identity tests presents a challenge. In this paper we report a new strategy for media identification tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Measurement of viscosity allows the fluidity of a cream to be gauged when it is actually applied by humans. These 2 techniques are a useful way to identify differences in forms of preparations [16] . The current findings suggested a correlation between assessment of physical properties and results of a sensory test, so determining a preparation’s physicochemical properties is a useful indicator of how the preparation will feel to humans [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of viscosity allows the fluidity of a cream to be gauged when it is actually applied by humans. These 2 techniques are a useful way to identify differences in forms of preparations [16] . The current findings suggested a correlation between assessment of physical properties and results of a sensory test, so determining a preparation’s physicochemical properties is a useful indicator of how the preparation will feel to humans [17] .…”
Section: Discussionmentioning
confidence: 99%
“…In other words, differences in fl attening lead to different amounts applied by patients in clinical settings and different feel on the skin, and these variations may affect the therapeutic effectiveness of the preparation. Near-infrared absorption spectroscopy, a nondestructive method of analysis, is a useful method of identifying differences in preparations (14). As the current study indicated, differences may affect skin penetration since preparations are used on areas with a thin layer of skin, like the face, to treat conditions like acne.…”
Section: Discussionmentioning
confidence: 89%
“…Differences in physical properties are surmised to cause differences in feel when ointments are actually applied. In such instances, NIR absorption spectroscopy, a non-destructive method of analysis, is a useful way to identify differences in preparations [21]. Physical assessment based on NIR absorption spectra leads to information on how preparations feel to patients and should provide indications of individual preferences.…”
Section: Discussionmentioning
confidence: 99%